Silencing E1A mRNA by RNA interference inhibits adenovirus replication - Chung, Y.-S. (Arch Virol, 2007)
The adenovirus family contains 51 human serotypes, and most human adenoviruses cause widespread respiratory tract infections. Adenovirus infections can result in severe complications in some cases, such as in adenovirus type 11 infection in immunocompromised patients. However, effective treatment methods for adenovirus infections are currently unavailable. This prompted the search for antiviral agents effective against adenovirus infections. In the present study, adenovirus E1A was targeted by RNA interference (RNAi) using synthetic small interfering RNAs (siRNAs) in an attempt to inhibit viral replication, since adenovirus E1A proteins are known to be involved in the transcriptional activation of the viral and cellular genes necessary for controlling the cell cycle and viral replication. The results indicated that the siRNAs effectively reduced the amount of adenovirus E1A mRNA and the levels of replicative intermediates. Additionally, siRNA-mediated gene silencing inhibited adenovirus replication by suppressing the E1A mRNA. These results suggest that the RNAi-mediated targeting of adenovirus E1A may have a potentially therapeutic effect in controlling adenovirus infections.